2016
DOI: 10.2169/internalmedicine.55.5694
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced Hypersensitivity Syndrome Accompanied by Pulmonary Lesions Exhibiting Centrilobular Nodular Shadows

Abstract: A 51-year-old woman diagnosed with Crohn's disease developed drug-induced hypersensitivity syndrome (DIHS) 12 and six weeks after starting the oral intake of mesalazine and trimethoprim/sulfamethoxazole, respectively. Chest CT showed centrilobular nodular shadows and a transbronchial lung biopsy (TBLB) revealed infiltration of inflammatory cells predominantly in the small pulmonary artery walls and bronchiolar walls. Regarding pulmonary lesions of DIHS, infiltrative shadows have sometimes been reported, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…2 and 3 ). (1) Diffuse micronodules in both lungs, with random distribution overall: This is different from the centrilobular distribution in DRESS syndrome reported by Sawata et al [ 38 ], which is a common pattern in hypersensitivity pneumonitis. The chest CT in our case showed that some nodules were in the pleural surface and interlobar fissure.…”
Section: Discussionmentioning
confidence: 68%
“…2 and 3 ). (1) Diffuse micronodules in both lungs, with random distribution overall: This is different from the centrilobular distribution in DRESS syndrome reported by Sawata et al [ 38 ], which is a common pattern in hypersensitivity pneumonitis. The chest CT in our case showed that some nodules were in the pleural surface and interlobar fissure.…”
Section: Discussionmentioning
confidence: 68%
“…Further, the positive tests to other compounds are compatible with a multiple drug hypersensitivity syndrome seen in DRESS. Interestingly, only two reports have described mesalazine-induced DRESS, occurring after prior exposure to sulfasalazine or sulfamethoxazole, and steroid therapy was necessary for clinical improvement 12 13…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory distress syndrome and pleural effusion are described in 31% and 22.7% of cases, respectively [ 2 ]. Bilateral nodules and centrilobular granular shadows were reported [ 1 , 3 , 4 ]. However, diffuse ground-glass opacities and ill-defined centrilobular nodules were present at the same time in the present case; they are unique and interesting features of this case.…”
Section: Discussionmentioning
confidence: 99%